KUALITAS JASA UNIT PELAKSANA TEKNIS PENGUJIAN SERTIFIKASI MUTU BARANG-LEMBAGA TEMBAKAU JEMBER - Shinta Setiadevi; Idqan Fahmi; Yossi Wibisono (School of Business, Bogor Agricultural University (SB-IPB), 2014)
This study aims to 1) analyze the methods and the customer satisfaction measurement results; 2) analyze the satisfaction of customer based on alternatives method by using Servqual approach and EPA; 3) Analyze the comparison between method and the customer satisfaction measurement results; 4) formulate recommendations for improvement of measurement methods and results of customer satisfaction in the Technical Implementation Unit Testing Certification-Institute for Product Quality Tobacco Jember. The processing of the data in this study was used the analysis of Service Quality (Servqual) and Expectation-Performance Analysis (EPA). The results of this study including: 1) Attributes which are considered sufficient by the IKM UPT measurement result are nine attributes: the effectiveness and efficiency of service, courtesy, friendliness, and obtain justice and other services; 2) Attribute selected as a top priority improvements based on EPA method is the availability of equipment and the latest technology; 3) Methods and results of measuring the level of customer satisfaction can be compared based on: the number of dimensions and attributes of service; outputs and implications of measurement methods; measurement results; 4) Recommendations for improvement, the management should renew equipment and the latest technology in testing and calibration laboratories, and increase equipment and the latest technology at the service of fumigation.Keywords: EPA, service quality, servqual, UPT PSMB-LT JemberABSTRAKPenelitian ini bertujuan 1) menganalisis metode dan hasil pengukuran indek kepuasan masyarakat; 2) menganalisis tingkat kepuasan pelanggan berdasarkan alternatif metode melalui pendekatan Servqual dan EPA; 3) menganalisis perbandingan antara metode dan hasil pengukuran kepuasan pelanggan; 4) merumuskan rekomendasi perbaikan metode dan hasil pengukuran kepuasan pelanggan pada Unit Pelaksana Teknis Pengujian Sertifikasi Mutu Barang-Lembaga Tembakau Jember. Pengolahan data penelitian menggunakan metode Service Quality (Servqual) dan metode Expectation-Performance Analysis (EPA). Hasil penelitian, yaitu 1) Atribut yang dinilai cukup oleh pelanggan hasil pengukuran IKM UPT terdapat sembilan artibut, antara lain: efektivitas dan efisiensi pelayanan, kesopanan, keramahan, dan keadilan mendapatkan pelayanan dan lainnya. 2) Atribut terpilih sebagai prioritas utama perbaikan berdasarkan metode EPA yaitu ketersediaan peralatan dan teknologi terbaru. 3) Metode dan hasil pengukuran tingkat kepuasan pelanggan dapat dibandingkan berdasarkan: jumlah dimensi dan atribut pelayanan; output dan implikasi metode pengukuran; hasil pengukuran. 4) Rekomendasi perbaikan, yaitu manajemen hendaknya memperbaharui peralatan dan teknologi terbaru pada laboratorium pengujian dan kalibrasi, serta menambah peralatan dan teknologi terbaru pada pelayanan fumigasi.Kata kunci: EPA, kualitas jasa, servqual, UPT PSMB-LT Jember